The Effects of Hybridization on Skeletal Morphology in Two Closely Related Populations of Rhesus Macaques (Macaca Mulatta): A Geometric Morphometric Approach - (:unkn) unknown (My University, 2022)
Precise identification and classification techniques are vital for the field of paleoanthropology to ensure that hominin fossilized remains are labeled accurately. The morphology of extinct hominin specimens will typically be compared to extant nonhuman primate species because of how closely related they are phylogenetically. Observable similarities in their morphological variation can be examined to infer which traits may be a result of evolution and this can update our understanding of their evolutionary relationships. The genus Macaca displays a level of morphological variation that is similar to that seen in the genus Homo, therefore macaques can be used as an analogous model to study morphological variation as it relates to hominin species. Geometric morphometrics is an approach that can quantitatively analyze the morphology of a specimen to infer questions relating to accurate identification and classification techniques. Recently, research has begun implementing a geometric morphometric approach to examine the morphological variation between- and within-species of macaques to develop a comparative dataset that can used with other closely related primate species, like hominins. Here, a sample of hybrid rhesus macaques (M. mulatta) are used to investigate the effects of hybridization on skeletal morphology and to expand the existing comparative dataset to offer a more inclusive model for hominin species. The skull and os coxa from the hybrid M. mulatta sample are quantitively examined via a geometric morphometric approach to determine whether specimens could be allocated to their correct taxonomic identification at the individual- and group-levels. In addition, the skull and os coxa are compared to determine which bone can more correctly allocate specimens. The goal of the thesis is to determine whether this quantitative approach can be used on a hybrid nonhuman primate sample as seen in previous research on purebred hominin and nonhuman primate samples. Results from the statistical analyses indicated that the hybrid M. mulatta were unable to be clearly differentiated based on their morphological variation. The results indicate that at this level of speciation, the quantitative approach is unable to differentiate specimens regardless of whether they are a purebred or hybrid individual. As a whole, the results from this thesis support the idea that there is a complex interaction between hybridization and morphology that has only started to be addressed in the literature. Future research is warranted to further examine the morphological variation of hybrid hominin and nonhuman primate species, which will ultimately update our understanding of evolutionary history.